Ability signals and rigorous coursework: Evidence from AP Calculus participation. (June 2022) - Avery, Christopher; Goodman, Joshua
Abstract: Large racial gaps in rigorous math coursework enrollment are a barrier to improving college completion rates and access to careers in STEM. Perceptions of the math abilities of underrepresented minority students, whether by themselves or their schools, may contribute to such gaps. A regression discontinuity design with data on all Massachusetts public school students shows how receiving a positive ability signal affects subsequent enrollment in advanced high school math coursework. For Black or Hispanic students, particularly those with low reading scores, being labeled as "Advanced" on a 10th grade math test substantially increases the likelihood of later Advanced Placement Calculus course- and exam-taking. White or Asian students and those from higher income high schools show no such effects. Understanding how ability signals affect students' and schools' decisions about assignment to coursework may suggest further ways to address gaps in such enrollment.